2016
DOI: 10.3174/ajnr.a4815
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Champagne Bottle Neck Sign in the Extracranial Carotid Arteries of Patients with Moyamoya Disease

Abstract: BACKGROUND AND PURPOSE:The champagne bottle neck sign represents a rapid reduction in the extracranial ICA diameters and is a characteristic feature of Moyamoya disease. However, the clinical significance of the champagne bottle neck sign is unclear. We investigated the relationship between the champagne bottle neck sign and the clinical and hemodynamic stages of Moyamoya disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
3
7
1
Order By: Relevance
“…The “bottleneck sign” was significantly associated with ipsilateral intracranial hemorrhage in MMD patients. Our findings coincided with those of Yasuda [ 11 ] and Wang et al [ 12 ]. We discovered that the ID of the ICA and the PSV of the ICA were independent parameters related to ipsilateral cerebral hemisphere stroke in MMD patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The “bottleneck sign” was significantly associated with ipsilateral intracranial hemorrhage in MMD patients. Our findings coincided with those of Yasuda [ 11 ] and Wang et al [ 12 ]. We discovered that the ID of the ICA and the PSV of the ICA were independent parameters related to ipsilateral cerebral hemisphere stroke in MMD patients.…”
Section: Discussionsupporting
confidence: 93%
“…Yasuda et al [ 11 ] used carotid ultrasound to measure the internal diameter of the ICA and the common carotid artery, and the results showed that with the progression of MMD and the reduction in cerebrovascular reactivity, the ratio of the ICA diameter to the common carotid artery diameter decreased. When the ratio of the two was less than 0.5, it was called the “bottleneck sign”.…”
Section: Discussionmentioning
confidence: 99%
“…Although most researchers have focused on the intracranial portions of the ICA and their branches in MMD, considering the histopathology aspects, MMD causes extracranial stenosis of the proximal portion of the ICA in some cases, the so-called bottleneck sign, which is a typical vascular finding of MMD (27). Yasuda et al (15) reported that the bottleneck sign began to appear in patients with Suzuki stage III or higher. Our results demonstrated that as the Suzuki stage advanced, the D of EICA decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al (14) demonstrated that flow volume (FV) of the internal carotid artery (ICA) detected by ultrasound was inversely correlated with Suzuki's grade. Yasuda et al (15) showed the ratio of the extracranial ICA (EICA) and common carotid artery diameters tended to be lower in symptomatic arteries than in asymptomatic arteries, the ratio decreased as cerebral vasoreactivity decreased. Wang et al (16) indicated that as the velocity of the PCA decrease, the ischemic lesions spread to a wider range and perfusion levels decreased from good to poor.…”
Section: Introductionmentioning
confidence: 99%
“…Although most researchers have focused on the intracranial portions of the ICA and their branches in MMD, considering the histopathology aspects, MMD causes extracranial stenosis of the proximal portion of the ICA in some cases, the so-called bottleneck sign, which is a typical vascular nding of MMD [23]. Yasuda et al reported that the bottleneck sign began to appear in patients with Suzuki stage or higher [24]. Our results demonstrated that as the Suzuki stage advanced, the diameter of EICA decreased.…”
Section: Discussionmentioning
confidence: 99%